In Vitro Fertilization in Central Java: Analysis of Influential Factor X Hospital - Dyah Ayu Prabandani; Sri Winarni; Septo Pawelas Arso (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The low utilization of IVF services can be caused by various factors influencing a person's perspective. People will consider various internal and external factors when using IVF services. The purpose of this study is to analyze the factors that influence the utilization of IVF services, as well as the development of marketing strategies and relevant marketing recommendations on IVF services at Hospital X of Central Java Province. The type of research used in this study is quantitative, with the data collection implementation using descriptive analytics and a logistic regression approach. Sampling in this study was carried out using a purposive sampling technique, with a sample size of 100 respondents. With logistic regression test results obtained. Results where service facilities (p=0.001), specialized health workers (p=0.001), fear of infertility (p=0.001), seriousness of infertility disease (p=0.028), benefits of undergoing IVF (p=0.001), quality of IVF services (p=0.001), cost (p=0.001), and introduction to IVF services (p=0.001). 001) These results indicate that the variables of predisposition, enabler, need, perceived benefits, perceived barriers, product, price, and promotion have a positive and significant effect on the utilization of IVF services at Hospital X in Central Java Province, only the variable of perceived severity is the only variable known to have no significant effect on the utilization of IVF services. This study shows that the problem of infertility is not a serious thing, so it is hoped that further research will strengthen the promotion of IVF so that people who experience infertility problems can be the initial service as a development of marketing strategies and relevant marketing recommendations for IVF services at X hospital. Keywords: In vitro fertilization, Infertility, Quality, Service